(untitled) (Cardiovascular Journal, 2016)
Background: In-hospital cardiac arrests are associated with poor survival despite basic and advanced life support measures. Objective of this study was to find out the profile and outcome of in-hospital cardiac arrest patients admitted to coronary care unit (CCU) of Chittagong Medical College Hospital. Methods: This prospective observational study was done on 243 consecutive patients developing cardiac arrest in CCU of Chittagong Medical College Hospital during a period of 1 year. Baseline demographics, clinical data, such as mode of arrest, timing of the event, duration of resuscitation were recorded. Basic and advanced life support measures were given according to AHA guidelines. The main outcomes were death and survival to hospital discharge with or without severe neurological disability. Results: There were 168 male and 75 female. Male:female ratio was 2.4:1.Mean age of the study population was 56.5±14.6 (range 23-76 yrs). Out of 243 arrest cases 108 (44.4%) had ventricular fibrillation(VF), 75(30.8%) had pulseless ventricular tachycardia(VT), 51 (20.8%) had pulseless electrical activity(PEA) and 9 patients (3.7%) had asystole. Mean±SD of time to defibrillation was 1.8±4.3min (range 0-30 min). Ninety eight (40.2%) patients had a return to spontaneous circulation, 71 (29.2%) survived up to 24 hours and only 46 (18.9%) patients survived to hospital discharge. Out of the 183 patients with VF and pulseless VT, 42 (22.9%) survived to hospital discharge. Survival following asystole and PEA were only 6.6% in each. Conclusion: Only 18.9% of cardiac arrest victims survived to hospital discharge. Initial cardiac arrest rhythm as VF and pulseless VT, a shorter time to defibrillation and location whether the event in monitored area were factors associated with a higher survival. Cardiovasc. j. 2016; 8(2): 123-127